Síndrome de Burnout en el personal de enfermería del hospital Manuel Ygnacio Monteros Loja en tiempos de pandemia por COVID-19 - Robles Valladares, Stefani Nicole (2023)
Burnout Syndrome (BS) is a psychological condition that results from chronic stress, it is a product of the conflictive interaction between the worker and his job. Its main characteristics are emotional exhaustion, depersonalization, and reduced personal accomplishment, which was aggravated by the COVID-19 pandemic. This pandemic increased work stressors, and make nurses suffer constant stress. For that reason, this research was carried out. The objective of this study was to identify nursing professionals affected by Burnout Syndrome in “Manuel Ygnacio Monteros Loja” Hospital during the COVID-19 pandemic. This is a quantitative, descriptive, and cross-sectional study. The research instrument was a survey based on the Maslach Burnout Inventory (MBI) questionnaire and it was applied to a sample of 121 nurses who worked at “Manuel Ygnacio Monteros” Hospital from August 2020 to August 2021. The results show that 44.6% of nurses who worked during COVID-19 had Burnout Syndrome, 66.90% had emotional exhaustion, 39.70% reported depersonalization and 42.1% manifested reduced personal accomplishment. In addition, it was found that there is no relationship between sociodemographic or occupational characteristics and Burnout Syndrome. In conclusion, Burnout Syndrome affected nursing professionals during the COVID-19 pandemic and it influenced their emotional environment negatively through symptoms of stress, fatigue, frustration, lack of empathy, and emotional hardening, which did not allow the adequate development of personal accomplishment